EVALUATION OF PARKING SPACES AT THE CLEANERS - Aldo Manggaranap Lumban Tobing (CERUCUK, 2021)
Sudimampir market is a complete shopping center in the city of Banjarmasin. Along with its running time, the market sudimampir into a crowded shopping mall visited by people of Banjarmasin and its surroundings for a complete and cost. Most visitors come the shop sudimampir market with a wholesale count.This research was conducted for analyzing the characteristics of the vehicle parked at the location of the study include: accumulation of parking, the average duration of parking, parking volume, the total number of its full vehicle parking ,and right parking  corner. Data collection was performed manually during holidays. Based on the survey results, in getting Parking Penatu is often not operating optimally by not using the appropriate SRP SNI and still perform manual calculations in the counter. Performance Laundry Parking can run optimally if SRP SNI and using the angle of 30 °. So it can produce 67 pieces SRP and able to accept 313 units wheeled vehicles 4. With so, parking can operate properly by its function, namely as a parking area in the city center.